Evidence for the utility of cfDNA plasma concentrations to predict disease severity in COVID-19: a retrospective pilot study - Hoeter,Katharina; Neuberger,Elmo; Fischer,Susanne; Herbst,Manuel; Juškevičiūtė,Ema; Enders,Kira; Rossmann,Heidi; Sprinzl,Martin F.; Simon,Perikles; Bodenstein,Marc; Schaefer,Michael (PeerJ, 2023)
Background COVID-19 is a worldwide pandemic caused by the highly infective SARS-CoV-2. There is a need for biomarkers not only for overall prognosis but also for predicting the response to treatments and thus for improvements in the clinical management of patients with COVID-19. Circulating cell-free DNA (cfDNA) has emerged as a promising biomarker in the assessment of various pathological conditions. The aim of this retrospective and observational pilot study was to investigate the range of cfDNA plasma concentrations in hospitalized COVID-19 patients during the first wave of SARS-CoV-2 infection, to relate them to established inflammatory parameters as a correlative biomarker for disease severity, and to compare them with plasma levels in a healthy control group. Methods Lithium-Heparin plasma samples were obtained from COVID-19 patients (n = 21) during hospitalization in the University Medical Centre of Mainz, Germany between March and June 2020, and the cfDNA concentrations were determined by quantitative PCR yielding amplicons of long interspersed nuclear elements (LINE-1). The cfDNA levels were compared with those of an uninfected control group (n = 19). Results Plasma cfDNA levels in COVID-19 patients ranged from 247.5 to 6,346.25 ng/ml and the mean concentration was 1,831 ± 1,388 ng/ml (± standard deviation), which was significantly different from the levels of the uninfected control group (p < 0.001). Regarding clinical complications, the highest correlation was found between cfDNA levels and the myositis (p = 0.049). In addition, cfDNA levels correlated with the “WHO clinical progression scale”. D-Dimer and C-reactive protein (CRP) were the clinical laboratory parameters with the highest correlations with cfDNA levels. Conclusion The results of this observational pilot study show a wide range in cfDNA plasma concentrations in patients with COVID-19 during the first wave of infection and confirm that cfDNA plasma concentrations serve as a predictive biomarker of disease severity in COVID-19.
Keywords: COVID-19; Sars-CoV-2; Cell free DNA; Organ dysfunction; Clinical outcome